THE EFFORTS TO IMPROVE THE ABILITY OF TEACHERS IN THE USE OF INFORMATION TECHNOLOGY IN MEDIA-BASED LEARNING THROUGH ACADEMIC SUPERVISION IN SDN RANGKAH I SURABAYA - Suharti Suharti (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
Supervision carried out through the PTS is a group supervision; yet the approach that will be used is the collaborative approach. The purpose of supervision is to improve the competence of teachers of the lower classes in planning thematic learning. Therefore, this research is titled as THE EFFORTS TO IMPROVE THE ABILITY OF TEACHERS IN THE USE OF INFORMATION TECHNOLOGY IN MEDIA-BASED LEARNING THROUGH ACADEMIC SUPERVISION IN SDN RANGKAH I SURABAYABased on the fact observation in the field as a school principal, the teachers seem to understand the performance evaluation and Academic Supervision that will be conducted by the supervisor. However, in fact, after the evaluation and supervision, many teachers remained confused regarding such evaluation and supervision.Through the activities of the Academic Supervision, the results of teachers' performance in designing learning implementation plans is observed with the stages that emphasize more on practical knowledge hence it would be easier to be told by composing the lesson plans.   The increase in teachers' performance in the activities of the Academic Supervision can be seen in cycle I and cycle II. Hence, they demonstrated a positive impact on the ability of teachers in managing the implementation of the learning